Pengembangan Aplikasi Biologi Sel Augmented Reality (BIOSAR) Berbasis Android Sebagai Media Pembelajaran Kelas XI SMA/MA: (Development of Android-Based Augmented Reality Cell Biology Application as Learning Media for Grade XI SMA/MA) - Khanan, Abdul; Wardhani , Irma Yuniar (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2024)
This study aims to (1) Determine the development of an Android-based Augmented Reality Cell Biology application as a learning medium, (2) Determine the feasibility of an Android-based Augmented Reality Cell Biology application as a learning medium. The method used is research and development (R&D) with a 4-D model adapted into 3-D (Define, Design, Develop). Data were collected through questionnaires, interviews, and documentation, with a saturated sampling technique. The subjects of the study were 31 students of class XI IPA MA YPKM Raden Fatah. The validation results showed a score of 92.36% from material experts and 95.31% from media experts, both in the